Replacement of antipsychotics as a method of preventing the formation of resistance in schizophrenia - G. E. Mazo; L. N. Gorobets (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2018)
The article is devoted to the methods of overcoming therapeutic resistance in patients with schizophrenia, in particular, during the replacement of antipsychotic therapy. The issues of lack of common views on the problem of resistance are discussed, and in connection with this - the lack of algorithms for managing patients with these problems. Data on the parameters of resistance determination (residual productive symptoms, side effects of antipsychotics, etc.) are given. Data on pharmacokinetic interactions of antipsychotics and their endocrine side effects are presented. The advantage of using ziprasidone for overcoming therapeutic resistance in patients with schizophrenia is shown.